Solid-Liquid Interface Thermal Resistance Affects the Evaporation Rate of Droplets from a Surface: A Study of Perfluorohexane on Chromium Using Molecular Dynamics and Continuum Theory - Han H.; Schlawitschek C.; Katyal N.; Stephan P.; Gambaryan-Roisman T.; Leroy F.; Müller-Plathe F. (My University, 2025)
We study the role of solid-liquid interface thermal resistance (Kapitza resistance) on the evaporation rate of droplets on a heated surface by using a multiscale combination of molecular dynamics (MD) simulations and analytical continuum theory. We parametrize the nonbonded interaction potential between perfluorohexane (C6F14) and a face-centered-cubic solid surface to reproduce the experimental wetting behavior of C6F14 on black chromium through the solid-liquid work of adhesion (quantity directly related to the wetting angle). The thermal conductances between C6F14 and (100) and (111) solid substrates are evaluated by a nonequilibrium molecular dynamics approach for a liquid pressure lower than 2 MPa. Finally, we examine the influence of the Kapitza resistance on evaporation of droplets in the vicinity of a three-phase contact line with continuum theory, where the thermal resistance of liquid layer is comparable with the Kapitza resistance. We determine the thermodynamic conditions under which the Kapitza resistance plays an important role in correctly predicting the evaporation heat flux. © 2017 American Chemical Society.